Pengaruh Penerimaan Dana ZISWAF, NPF Gross, dan Pendapatan Mudharabah terhadap ROE Dengan Firm Size sebagai Variabel Moderasi pada Perbankan Syariah di Indonesia Periode 2018 Q1-2023 Q3. - Firdaus, Violinda Syahgaria; Budianto, Eka Wahyu Hestya (Istithmar, 2024)
This research aims to analyze the effect of receiving Zakat, Infaq, Alms, and Waqf (ZISWAF), Gross Non-Performing Financing (NPF), and Mudharabah Income on Return on Equity (ROE) with Firm Size as a moderation variable in Islamic Banking in Indonesia during the period 2018.Q1 to 2023.Q3. The sampling technique used was purposive sampling, with a total sample of 115 companies for 5 years.  The data analysis techniques used are Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the Eviews 12 application. The results showed that the receipt of ZISWAF funds had a significant negative effect on ROE in the financial sector for the period 2018.Q1-2023. Q3. Gross NPF has a significant negative effect on ROE in the financial sector for the period 2018.Q1-2023. Q3. Mudharabah revenue has a significant negative impact on ROE in the financial sector for the period 2018.Q1-2023. Q3. Firm Size is able to moderate the effect of receiving ZISWAF funds on ROE in the financial sector for the 2018.Q1-2023 period. Q3. Firm Size is able to moderate the influence of NPF Gross on ROE in the financial sector for the period 2018.Q1-2023. Q3. Firm Size is able to moderate the effect of mudharabah income on ROE in the financial sector for the 2018.Q1-2023 period. Q3.